The Protective Effects of Virgin Coconut Oil on High-Fat Diet Induced Rat Liver - M Arsang (Babol University of Medical Sciences, 2020)
BACKGROUND AND OBJECTIVE: A high-fat diet can disrupt the antioxidant system and damage the liver. One of the most important ways to control non-alcoholic fatty liver is to use natural compounds with antioxidant properties. Therefore, this study was performed to evaluate the effect of coconut oil on cholesterol, triglyceride and antioxidant status in high-fat diet- induced rat liver. METHODS: In this experimental study, 30 male rats were randomly divided into 6 groups of 5 including: 1) control group, 2 and 3) control+10% and 8% virgin coconut oil, 4) only receiving high fat diet, and 5 and 6) receiving high fat diet+10% and 8% virgin coconut oil. Coconut oil was prepared daily and mixed with animal food. At the end of the study, the rats were anesthetized and liver tissue was isolated and used for antioxidant tests. FINDINGS: In this study, the levels of triglyceride (159±11.5) in the high-fat diet group increased significantly compared to the control (64±4.2) (p<0.001). Treatment of high-fat diet group with coconut oil at doses of 8% (104.5±9.1) and 10% (97.5±8.2) was able to reduce triglyceride levels (p<0.05) significantly. Cholesterol (118±6.7) in the high-fat diet group increased significantly compared to the control (60±6.6) (p<0.001). Treatment of high-fat diet group with coconut oil at a dose of 10% (94±5.3) was able to reduce cholesterol (p<0.01) significantly. CONCLUSION: According to the results of this study, virgin coconut oil can be useful in the treatment of fatty liver by reducing lipids and increasing antioxidants.